Serviço social na saúde coletiva: as possibilidades de materialização do conceito ampliado de saúde - (:unkn) unknown (Universidade Federal do Pampa, 2018)
This article has as central theme social service in collective health and aims to analyse the work of th social worker in the process of materialisation of the extended concept of health, to emphasize the importance of this professional in Primary Health Care (PHC). Social Service, as a human and social science area and as a health profession, contributes, through its instruments, to social rights effectiveness, highlighting health care rights, in its broader meaning. The motivation for this study comes through the experience as a resident in the Multi-professional Integrated Residency Program in Collective Health by Universidade Federal do Pampa (Unipampa/RS). This article was elaborated based on a bibliographical research, which is characterized as qualitative with exploratory nature, also has its structure based on dialectical-critical method. Scientific production on the theme is still incipient, therefore, the knowledge about social worker contributions in collective health is still a road to discover. It is considered that these contributions are instituted by the fact that this professional being able to focus, through their area of knowledge, in transforming the reality, extending the view to different aspects of life that condition and determine the health-illness process of the subjects, as well as questioning, in a propositional way, traditional practices in a field where biological knowledge prevails.
Social service in collective health: the possibilities of materialization of extended concept of health
Keywords: Assistente Social; Saúde Coletiva; Conceito ampliado de saúde; Social Worker; Collective Health; Extended concept of health; Atenção básica; Atenção primária a saúde; APS; CNPQ::CIENCIAS SOCIAIS APLICADAS